2016
DOI: 10.5056/jnm16001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Visceral Hypersensitivity in Irritable Bowel Syndrome: Pharmacological Targets and Novel Treatments

Abstract: Irritable bowel syndrome (IBS) is the most common disorder referred to gastroenterologists and is characterized by altered bowel habits, abdominal pain, and bloating. Visceral hypersensitivity (VH) is a multifactorial process that may occur within the peripheral or central nervous systems and plays a principal role in the etiology of IBS symptoms. The pharmacological studies on selective drugs based on targeting specific ligands can provide novel therapies for modulation of persistent visceral hyperalgesia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
128
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(141 citation statements)
references
References 151 publications
(141 reference statements)
2
128
0
11
Order By: Relevance
“…19,20 In this review we will discuss the hypothesis that visceral pain disorders result from abnormalities of the brain-gut axis due to "multiple hits" which include external risk factors such as abuse history and chronic psychological stress in adulthood which together are capable of sensitizing the stress response system to cause alterations in no-An important aspect to enhancing our understanding of IBS pathophysiology is the knowledge that IBS patients exhibit visceral hypersensitivity characterized by hyperalgesia and allodynia in a subset of IBS patients ranging from 33-90% of patients with IBS depending on the study. [37][38][39][40][41][42] Although the cause of visceral hypersensitivity is unknown, clinical studies have shown that chronic stress worsens IBS symptomatology and ELS serves as a risk factor for IBS. [43][44][45][46] The sympatho-medullary and the HPA axes are activated by exposure to stress; the sympatho-medullary axis releases epinephrine from the adrenal medulla, to allow the organism to "fight" or "flee" from a threat, whilst activation of the HPA axis releases cortisol (or corticosterone [CORT] in rodents) from the adrenal cortex to mobilize reserves of glucose with the goal of replenishing the expended sympatho-medullary system.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In this review we will discuss the hypothesis that visceral pain disorders result from abnormalities of the brain-gut axis due to "multiple hits" which include external risk factors such as abuse history and chronic psychological stress in adulthood which together are capable of sensitizing the stress response system to cause alterations in no-An important aspect to enhancing our understanding of IBS pathophysiology is the knowledge that IBS patients exhibit visceral hypersensitivity characterized by hyperalgesia and allodynia in a subset of IBS patients ranging from 33-90% of patients with IBS depending on the study. [37][38][39][40][41][42] Although the cause of visceral hypersensitivity is unknown, clinical studies have shown that chronic stress worsens IBS symptomatology and ELS serves as a risk factor for IBS. [43][44][45][46] The sympatho-medullary and the HPA axes are activated by exposure to stress; the sympatho-medullary axis releases epinephrine from the adrenal medulla, to allow the organism to "fight" or "flee" from a threat, whilst activation of the HPA axis releases cortisol (or corticosterone [CORT] in rodents) from the adrenal cortex to mobilize reserves of glucose with the goal of replenishing the expended sympatho-medullary system.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Visceral hypersensitivity is one important pathophysiological mechanism in the generation of IBS. 10,11 Many previous experimental studies found that EALs such as maternal separation (MS) can induce adult visceral hypersensitivity. 5,6,12 However, the effect of EALs on the different age stages from childhood to adulthood is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Как известно, при отсутствии патологических изменений обычное растяжение или сокращение полого органа не ощущается человеком. Нарушенная чувствитель-ность в ответ на нормальные физиологические стиму-лы рассматривается как ВГЧ [1]. При наличии ВГЧ у пациентов с СРК отмечается усиленная перцепция (ощущение, восприятие) в ответ на механические воз-действия на кишечник, что больным воспринимается как боль или дискомфорт в животе [2].…”
unclassified
“…Гипералгезия -это состояние, при котором импульсы, которые могут вы-звать в обычных условиях боль, воспринимаются как более интенсивная боль. Аллодиния -это состояние, при котором боль отмечается из-за импульсов, не спо-собных в обычных условиях вызывать болевые ощу-щения [1]. Таким образом, у больных с СРК при ВГЧ отмечается сниженный порог восприятия импульсов из кишечника.…”
unclassified
See 1 more Smart Citation